Wild edible plants used by the Indigenous communities of the Trans-Himalayan region of Ladakh, India - Batool, Zohra; Gairola, Sumeet (Ethnobotany Research and Applications, 2025)
Trans-Himalayan region, evolved traditional knowledge to identify, harvest, use, and manage wild edible plants (WEPs). WEPs are vital in meeting nutritional needs and surviving food scarcity during harsh winters. However, WEPs and related traditional knowledge in the region have declined recently due to multiple human, climatic, and environmental factors. Hence, the present study aimed to document traditional knowledge and diversity of WEPs, the current threat status of WEPs, identify species with maximum usage and quantify consensus among the informants in Ladakh. Methods: The study was conducted in 12 villages of five regions, viz., Changthang, Kargil, Nubra, Leh, and Zanskar of Ladakh, between 2019 and 2022. 60 participants (35 men and 25 women) were interviewed using open and semi-structured questionnaires. Results: Fifty-two wild edible plants belonging to 25 families and 40 genera were recorded as being used for edible purposes, with 288 use reports (UR). The most utilized species were Thymus linearis Benth. (UR=38), and Capparis spinosa L. (UR=31). The recorded species' cultural index (CI) ranged from 0.03 to 0.63. The highest informant consensus factor (ICF) was reported for the vegetable category (ICF=0.82), followed by traditional dishes and flavoring agents (ICF=0.80 each). Based on the IUCN Red List and North-Western Himalayan (NWH) database, recorded WEPs included one critically endangered, two endangered, and three vulnerable species. Conclusions: The current study reported 52 wild edible plants of Ladakh, highlighting their rich diversity and importance in traditional cuisine. The findings of this study can be utilized in the future to identify individual nutritional value and antioxidant activities of species with high consensus and cultural significance. Keywords: Wild edible plants; Ladakh; Traditional knowledge; Ethnobotany; Informant consensus factor